The New Scientific Atheism - Cañón Loyes, Camino (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2016)
When we speak of scientific atheism today, we are exploring new ways to talk about issues that were already present in the occidental culture but now appear with new relevance. First, we offer a descriptive approach to the New Atheism and a presentation of its principal authors. In a critical way, we analyze the syntactic, semantic and pragmatic levels of religious beliefs in the discourse of these authors in order to show the strength and weakness of religious belief.Their unlimited confidence in reason is especially expressed in the naturalization project that reaches religion and the numinous. Emerge in a new way the «naturalized human nature», as not only is governed by the laws of evolution, but also by human decision through increasingly powerful technologies. We offer three metaphors to show some ways forward in the relationship between science and religion are offered, and in particular, between science and Christian faith.
Keywords: New Atheism; naturalism; scientific reason; science and Christian faith.